1997
DOI: 10.1029/96jc02803
|View full text |Cite
|
Sign up to set email alerts
|

Wind‐forced modeling studies of currents, meanders, and eddies in the California Current system

Abstract: Abstract. This process-oriented study of the California Current system (CCS) uses a high-resolution, multilevel, primitive equation ocean model on a/3 plane to isolate the response of that eastern boundary oceanic regime to temporal and spatially varying wind forcing. To study the generation, evolution, and maintenance of many of the observed features such as currents, meanders, and eddies in the CCS, the model is forced from rest with seasonal climatological winds. In response to the prevailing wind direction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
83
2
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(97 citation statements)
references
References 53 publications
(38 reference statements)
10
83
2
2
Order By: Relevance
“…The generation of a poleward undercurrent along the west coast is consistent with previous process-oriented modeling studies which have shown that a poleward undercurrent can be generated due to meridional variability in the predominantly equatorward wind stress (Batteen et al, 1989) and/or to the planetary beta effect (e.g., McCreary et al, 1986;Batteen, 1997). The beta effect allows the existence of freely propagating planetary waves, i.e., Rossby waves (Gill, 1982).…”
Section: Wind Forcing Over a Flat Bottomsupporting
confidence: 75%
“…The generation of a poleward undercurrent along the west coast is consistent with previous process-oriented modeling studies which have shown that a poleward undercurrent can be generated due to meridional variability in the predominantly equatorward wind stress (Batteen et al, 1989) and/or to the planetary beta effect (e.g., McCreary et al, 1986;Batteen, 1997). The beta effect allows the existence of freely propagating planetary waves, i.e., Rossby waves (Gill, 1982).…”
Section: Wind Forcing Over a Flat Bottomsupporting
confidence: 75%
“…Note that the present diagnosis is somewhat different from the traditional energy diagnosis, as, for instance, applied recently by Batteen [1997] and others [Treguier, 1992;Ivchenko et al, 1997]. The present analysis concludes that horizontal (barotropic) and vertical (baroclinic) shear instabilities are unimportant throughout the whole simulation period, while the frontal instability and the mixed frontalconventional baroclinic instability are of equal importance, even during the growth phase.…”
Section: Discussion Of Quasi-equilibrium Phasementioning
confidence: 74%
“…However, in run B the effect of an irregular coastline is still present. As noted originally by Arthur [i965] and also observed by Batteen [1997], an alongshore variability in the linear wind-driven upwelling is to be expected when irregularities in the coastline geometry are introduced, even under uniform wind forcing. Thus the buildup of the upwelling front will exhibit an alongshore variability, which in turn will have an influence on the timing of the onset of instabilities.…”
Section: Methodsmentioning
confidence: 85%
See 2 more Smart Citations